Serum Ferritin as a Marker of Systemic Inflammation in Patients with Poly cystic ovary. - Ali, Anwar; Fatima, Fatima; Rahman, Obaid Ur; Shuaib, Faiza; Ahmed, Ayaz; Muntaha, Sedra tul (Journal of Neonatal Surgery, 2025)
Background: Polycystic ovary syndrome (PCOS) has far-reaching impacts in society, including amenorrhea, excess androgens, and metabolic syndrome, which are all indicators of this syndrome. Most recently, the role of chronic low-grade inflammation in the pathogenesis of the syndrome has gained traction. Ferritin, an inflammatory protein, reflects an underlying inflammatory state in the metabolic syndrome and is thus proposed as an inexpensive and accurate biomarker to evaluate systemic inflammation in the syndrome. Objectives: To assess serum ferritin concentrations in women with polycystic ovary syndrome (PCOS), compare these levels with those of healthy control participants, and evaluate the associations between ferritin and inflammatory markers, insulin resistance, and key metabolic parameters. Methodology: This cross-sectional study conducted at Department of Obstetrics and Gynecology, Bacha Khan Medical College, Mardan Medical Complex Mardan from Jan 2025 to June 2025.women between the ages of 18 and 40 who had the diagnosis of PCOS according to the Rotterdam criteria were included. Healthy, age-matched women were included as controls. The following laboratory assessments were made: serum ferritin, C-reactive protein (CRP), fasting glucose, fasting insulin, and a lipid profile. The HOMA-IR score was utilized to assess insulin resistance. Data analysis was conducted on the 24.0 version of SPSS using t-tests and correlation analysis at the 0.05 significance level. Results: A total of 60 women with PCOS were included in the study. The mean age was 26.8 ± 4.9 years. Serum ferritin levels were significantly elevated in PCOS patients compared with age-matched healthy controls (p < 0.001). Higher ferritin concentrations showed positive correlations with CRP (p = 0.002), fasting insulin (p = 0.01), HOMA-IR (p = 0.003), and triglycerides (p = 0.02), indicating increased inflammatory and metabolic burden. Conclusion: Elevated serum ferritin was noted in women with PCOS and was strongly associated with systemic inflammation and insulin resistance. Its positive correlation with metabolic parameters suggests that ferritin may be a valuable, readily available marker of metabolic and inflammatory risk. Routine ferritin measurements improve patient evaluations, enhance clinical management of PCOS, and aid in planning preventive measures.